Kabupaten Halmahera Selatan : Sektor Unggulan Dan Perubahan Struktur Ekonomi - Musdar Muhammad; Muhammad Kamal; Suratno Amiro (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of the study was to determine the economic sector and economic change in Halmahera Seletan district, secondary data from 2019-2023, descriptive quantitative research methods, LQ and SSA analysis tools. The results of the study, the economic sector which is the basic sector is in the agriculture, forestry and fisheries economic sector, the mining and quarrying sector, the manufacturing sector, the water supply sector, waste management, waste and recycling, the construction sector, the wholesale and retail trade sector, car and motorcycle repair, and the real estate sector, the education services sector, the health services sector and social activities, the economic sector is the basic sector but the regional component of the economic sector in South Halmahera district does not have economic growth, But in the proportional growth component (proportional shift) is a developed economic sector to be developed, the agriculture, forestry and fisheries sector, the mining and quarrying sector, the processing industry sector, the water supply sector, waste management, waste and recycling, the construction sector, the wholesale and retail trade sector, car and motorcycle repair is a basic sector but in the competitiveness share this sector is not a sector that has high economic competitiveness within the South Halmahera district area and economic sectors from other regions.)